CHALLENGES IN REALIZING THE SOFTWARE APPLICATIONS BASED ON MICRO SERVICES ARCHITECTURE - Dr. Kamlendu Kumar Pandey , Dr. Dhaval Joshi (International Journal of Advanced Science and Technology, 2020)
Micro Services Architecture is the emerging design pattern to create light weight, efficient, scalable and collaborative real-world software applications. All top IT companies, major communities, tool chain developers are creating the environment to implement this architecture. This breaks the earlier monolithic implementations and goes for a truly distributed and collaborative way of execution. Though it gives lot of promises there are many aspects which are to be looked into as challenges to implement micro services. This paper digs into all those challenges in a systematic way with real world examples. In order to see the quality of implementations several questions are asked to understand the real problem areas of implementation. A measurable matrix is worked out for the level of implementation.